INASAR Deployment Governance in International Earthquake Response: Türkiye 2023 and Myanmar 2025 - Jeremy Putra Pratama; Taqwa Putra Budi Purnomo Sidi Hiram; Abdul Haris Achadi (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study examines the governance of Indonesia’s urban search and rescue team (INASAR/Basarnas) in the 2023 Türkiye earthquake and the 2025 Myanmar earthquake, where life-saving operations were highly time-sensitive. Anchored in the 72-hour golden time, it addresses a central question: why did a classified international USAR team with early access to situational information become operational only around day six in both missions? Using a qualitative explanatory multi-case design, the study draws on semi-structured interviews, mission reports, and operational guidelines. The analysis combines event logs, process mapping, and directed thematic analysis to trace the pathway from external trigger to initial operational readiness. The findings show that the delays were not caused by the absence of early information, weak technical capacity, or the lack of international requests. Instead, they emerged from a serial chain of governance bottlenecks involving delayed decision conversion, layered resource authorization, sequential financing access, the bundling of USAR with non-USAR assistance, cross-border clearance, and personnel-equipment desynchronization in practice. These processes reduced arrival-to-initial-readiness and narrowed the team’s potential life-saving contribution. The study proposes the concept of serial bottleneck deployment governance to explain how deployment delays are produced through interconnected governance processes on the sending-state side. It concludes that more effective deployment requires a dedicated USAR decision track, readiness financing, stronger standing readiness, and a more modular deployment design under emergency conditions.